Parameter Estimation of a Hyperelastic Constitutive Model for the Description of Polyurethane Foam in Large Deformation. Issue 1 (January 2013) - Ju, M.L.; Mezghani, S.; Jmal, H.; Dupuis, R.; Aubry, E.
Polyurethane foam is widely used in such areas as the automotive industry and sport, and in the field of packaging because of its low stiffness, high compressibility and its ability to absorb strain energy. The quasi-static behaviours of polyurethane foam are highly nonlinear and elastic. This paper demonstrates that the nonlinear elastic mechanical behaviour of compressible polyurethane foam during the loading and unloading quasi-static compression tests can be described by applying Ogden's modified model. The experimental data from a uniaxial compression of three types of polyurethane foam in three different strain rates are used for parameter identification. A nonlinear optimization method helps to ensure that the parameters are satisfied with stability conditions. Thanks to the optimized parameter results, the numerical simulations agree with the experimental data. Finally, the errors between the model results and the experimental results are analyzed and the unloading phases are discussed in detail.